UN Women's Role in Addressing Gender-based Violence in Indonesia during the Covid-19 Pandemic: Norm Entrepreneur Analysis - Reydinata, Rayhan (JLAST : Journal of Law and Social Transformation, 2025)
This study analyzes the role of UN Women as a norm entrepreneur in addressing gender-based violence (GBV) in Indonesia during the COVID-19 pandemic. Using a qualitative approach and literature review, the research explores UN Women's efforts in promoting norms of gender equality, women's empowerment, and the eradication of GBV. The COVID-19 pandemic exacerbated GBV in Indonesia due to mobility restrictions, socio-economic pressures, and patriarchal culture. In response, UN Women launched initiatives such as the DELILA reporting system, online counseling services in collaboration with Yayasan Pulih, and educational campaigns. This study concludes that UN Women's efforts significantly contribute to social change and accelerate the achievement of Sustainable Development Goal (SDG) 5. However, challenges such as the digital divide and patriarchal norms require further efforts to ensure the sustainability of these programs.